Boon. Gerard K. Technology and employment in footwear manufacturing. Holanda : Sythoff and Noordhoff, 1980. 232 p. - Rattner, Henrique (Estudios Demográficos y Urbanos, 1983)
BOON, GERARD K, Technology and employment in footwear manufacturing, Holanda, Sythoff and Noordhoff, 1980.